Desenvolvimento de filmes biodegradáveis baseados em pectina e nanofibras de celulose funcionalizadas - Franco, Giuliana Thalina (2019)
Renewable polymers are an interesting alternative to synthetic polymers from petrochemical sources. The work aims at the development of nanocomposite films based on pectin and functionalized cellulose nanofibers. The functionalization of nanofibers ocurred by oxidation, mediated by 2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO), and by cationization, through nucleophilic substitution by glycidyltrimethylammonium chloride (GTMAC), in order to provide interactions with the pectic matrix. Low methoxylation pectin showed Zeta potentials around -35 mV at pH close to 7, which promotes the arrangement of surface charges in the polymer matrix. Nanocomposite films were obtained by discontinuous casting from aqueous suspensions of pectin and cellulose nanofibers, which were characterized for their thermal, mechanical, antimicrobial, rheological and structural properties. The functionalization of the NFC promoted the decrease of the crystallinity due to its influence on the packaging of cellulosic chains, as well as the decrease of the viscosity of the filmogenic suspensions. Antimicrobial analyzes showed inhibition of Escherichia coli growth in filmogenic suspensions containing 1 and 5% oxidized and cationized NFC, respectively. Mechanical tests showed that incorporation of NFC promoted an increase of 2 in tensile strength and of 3 in rupture elongation, which allowed the production of nanocomposites with better mechanical performance.